Differences between the Kinetically Preferred States of LiFePO4 during Charging and Discharging Observed Using In Situ X-ray Diffraction Measurements. Issue 6 (18th April 2017) - Satou, Yoshinori; Komine, Shigeki; Itou, Shinich; Asai, Hideo; Yao, Takeshi; Takai, Shigeomi
Abstract : In-situ X-ray diffraction measurements were performed on LiFePO4 during charging and discharging using synchrotron radiation to elucidate the origin of the hysteresis in the kinetic mechanisms of the charging and discharging processes. The experimental results clearly showed that fewer intermediate phases were formed during the charging process than the discharging process, in keeping with previous studies. Further, during the discharging process, a Li-containing Li-lean phase and a Li-defective Li-rich phase with large lattice spacing were generated kinetically in the initial stage. Based on these results, we propose a new model for the hysteresis between the charging and discharging processes.